Influência do exercício físico no remodelamento cardíaco de ratos espontaneamente hipertensos - Pagan, Luana Urbano [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Introduction: The systemic arterial hypertension (SAH) is a highly prevalent disease worldwide. SAH induces cardiac alterations characterized by left ventricular (LV) hypertrophy, ventricular diastolic and / or systolic dysfunction and clinical manifestations such as arrhythmia and heart failure (HF). The process by which chronic hemodynamic overload, such as hypertension, induces these alterations is known as cardiac remodeling. Within this process, changes in interstitial collagen matrix play a fundamental role. The pressure overload caused by hypertension may lead to changes in collagen architecture increasing myocardial fibrosis and stiffness, with consequent LV diastolic dysfunction. Physical exercise has shown benefit as coadjuvant measure in the treatment of HF, but its effect on cardiac remodeling, particularly associated with uncontrolled hypertension, remains unclear. Therefore, the aim of this study was to evaluate the influence of physical training on cardiac remodeling in spontaneously hypertensive rats (SHR) during the development of HF. Methods: Four experimental groups were constituted as follows: male SHR, 16 month old, sedentary (SHR-SED, n=25); exercised male SHR (SHR-EX, n=25), sedentary control male rats Wistar-Kyoto (WKY-SED, n=17); and exercised male WKY (WKYEX, n=18). Animals from the exercised groups were submitted to a treadmill exercise protocol, five days a week, for four months. The in vivo cardiac structural and functional evaluation was performed by echocardiography. The in vitro myocardial function was evaluated by isolated left ventricular papillary muscle preparations. LV tissue samples were obtained for quantification of hydroxyproline concentration, histological analysis and quantification of interstitial collagen soluble and insoluble fractions. Genic expression of collagen types I and III and lysyl oxidase was assessed by real time RT-PCR. Comparisons between ...

Introdução: A hipertensão arterial sistêmica (HAS) constitui doença de alta prevalência em nosso meio. A HAS induz alterações cardíacas caracterizadas por hipertrofia do ventrículo esquerdo (VE), disfunção ventricular diastólica e/ou sistólica e manifestações clínicas como arritmia e insuficiência cardíaca (IC). O processo pelo qual sobrecargas hemodinâmicas crônicas, como a HAS, induzem tais alterações é denominado remodelamento cardíaco. Dentro desse processo, alterações da matriz colágena intersticial apresentam papel fundamental. A sobrecarga de pressão causada pela HAS pode gerar mudança na arquitetura do colágeno e favorecer o aumento de fibrose e rigidez miocárdica, com consequente disfunção diastólica do VE. O exercício físico tem mostrado benefício como medida coadjuvante no tratamento da IC, porém seu efeito sobre o remodelamento cardíaco, particularmente associado à HAS não controlada, ainda não está esclarecido. Dessa forma, o objetivo desse estudo foi avaliar a influência do treinamento físico sobre o remodelamento cardíaco de ratos espontaneamente hipertensos na fase de desenvolvimento da IC. Métodos: Foram constituídos os seguintes grupos experimentais: ratos espontaneamente hipertensos machos, com 16 meses de idade, sedentários (SHR-SED, n=25); SHR exercitados machos (SHREX, n=25); ratos controle Wistar-Kyoto sedentários machos (WKY-SED, n=17) e; WKY exercitados machos (WKY-EX, n=18). Os animais dos grupos exercitados foram submetidos a protocolo de exercício em esteira, cinco dias por semana, durante quatro meses. A avaliação estrutural e funcional in vivo do coração foi realizada por meio de ecocardiograma. A função miocárdica in vitro foi avaliada em preparações de músculo papilar isolado do VE. Amostras de tecido do VE foram obtidas para quantificação de hidroxiprolina, análises histológicas e quantificação das frações solúvel e insolúvel do colágeno ...
Keywords: Hipertensão - Tratamento; Exercícios físicos - Uso terapêutico; Insuficiencia cardiaca; Rato como animal de laboratorio; Hypertension